Canonical WNT/β-Catenin Signaling Plays a Subordinate Role in Rhabdomyosarcomas - Ragab, Nada; Viehweger, Florian; Bauer, Julia; Geyer, Natalie; Yang, Mingya; Seils, Anna; Belharazem, Djeda; Brembeck, Felix H.; Schildhaus, Hans-Ulrich; Marx, Alexander; Hahn, Heidi; Simon-Keller, Katja (Frontiers in Pediatrics, 2018)
The development of skeletal muscle from immature precursors is partially driven by canonical WNT/β-catenin signaling. Rhabdomyosarcomas (RMS) are immature skeletal muscle-like, highly lethal cancers with a variably pronounced blockade of muscle differentiation. To investigate whether canonical β-catenin signaling in RMS is involved in differentiation and aggressiveness of RMS, we analyzed the effects of WNT3A and of a siRNA-mediated and pharmacologically induced β catenin knock-down on proliferation, apoptosis and differentiation of embryonal and alveolar RMS cell lines. While the canonical WNT pathway was maintained in all cell lines as shown by WNT3A induced AXIN expression, more distal steps including transcriptional activation of its key target genes were consistently impaired. In addition, activation or inhibition of canonical WNT/β catenin only moderately affected proliferation, apoptosis or myodifferentiation of the RMS tumor cells and a conditional knockout of β-catenin in RMS of Ptchdel/+ mice did not alter RMS incidence or multiplicity. Together we assume that canonical WNT/β-catenin signaling is of no importance for RMS proliferation, apoptosis or differentiation and thus aggressiveness of this malignant childhood tumor.